Slope-shelf faunal link and unreported diversity off Nova Scotia: Evidence from polychaete data. (August 2018) - Neal, Lenka; Taboada, Sergio; Woodall, Lucy C.
Abstract: Deep-water sedimentary habitats off Nova Scotia have only rarely been explored. The topographically and oceanographically complex shelf of Nova Scotia harbours two interesting topographic features, Emerald Basin, a sedimentary habitat reaching greater depths (max of 270 m) than the surrounding shelf and the Gully, the largest canyon in NW Atlantic. Emerald Basin is exposed to upwellings of slope water and harbours predominantly deep-sea hexactinellid sponges. Such distributional pattern resembles "deep-water emergence". In this study an abundant benthic group, the polychaetes, were selected to test for such deep-water faunal link. Qualitative boxcores were collected from Emerald Basin (180 m depth, N = 5) and the adjacent Gully Canyon (1600 m, N = 3). At species level, there was no overlap in distribution between Emerald Basin (N = 73, S=29) and Gully Canyon (N = 351, S = 60) fauna based on morphological assessment of all specimens and molecular analysis (COI and 16S markers) of selected morphotypes. In an alternative approach, Multivariate analysis (nMDS, Cluster Analysis) of incidence data for polychaete genera (N = 179) from 24 Atlantic sites (5–1600 m) was carried out. These results showed a greater similarity of Emerald Basin polychaetes to bathyal sites (400–1000 m), particularly the 680 m site off Nova Scotia rather than shelf sites (5–80 m), including those on the Nova Scotia shelf. Thus, at 1600 m, the Gully Canyon samples were likely "too deep" for our comparative purposes and depths of < 1000 m should be targeted in the future. Our data also provide the first published assessment of polychaete diversity from the Gully Canyon, suggesting the presence of a diverse assemblage (S = 60). Unusually for a deep-sea site, the Gully Canyon polychaetes are mostly known taxa with wider distribution across bathyal NW Atlantic. Additionally, our molecular data provide an interesting insights into the distribution of several polychaete species commonly found in deep-sea (e.g Aurospio dibranchiata Maciolek, 1981; Ophelina abranchiata Støp-Bowitz, 1948) suggesting wide geographical distribution for some but revealing species complexes for others. Highlights: Emerald Basin polychaeta fauna sampled at depths of 180 m is deep-sea in character based on analysis of polychaete genera. Gully Canyon, sampled at 1600 m, harbours diverse polychaete assemblage with many species known from wider deep NW Atlantic. There was no overlap in species distribution between the Emerald Basin and Gully Canyon based molecular data. Aurospio dibranchiata and Ophelina abranchiata represent species complexes based on molecular data. Two genetic clades of Aurospio dibranchiata were separated by depth rather than geographical distance. Certacephale loveni was shown to have NW and NE Atlantic distribution as supported by molecular data.